Policy of vaccination of "fragile children": Results of a survey of 14 Italian children's hospitals - Désirée Caselli; Maurizio Aricò; Fabiana Fiasca; Silvio Tafuri (Taylor & Francis Group, 2023)
Children with chronic disease are at higher risk of invasive infectious disease, including several vaccine-preventable infections. The Italian Association of Pediatric Hospitals (AOPI) carried out a survey of immunization practices: 14/16 AOPI hospitals completed the survey; 50% of them include 100-199 beds, while 21% have <100 beds. In 12/14 hospitals (86%) all vaccinations included in the National Immunization Plan (plus influenza e COVID-19 vaccines) are available for inpatients, in selected wards (n = 4), on single pediatrician initiative (n = 3), by a centralized in-hospital immunization service (n = 2), and the remaining 3 in a "protected vaccination area" or in a COVID-19 pathway. The wards in which vaccination is more frequently offered to in-patients are: General Pediatrics, Neonatology, Pediatric Hematology & Oncology, Pediatric Diabetology, Pediatric Cardiology, and Pediatric Infectious Diseases (range, 58% to 83%). In 58% of vaccinating hospitals, <500 vaccinations/year are reported, while in 17% this number is >2,000/year. A COVID-19 vaccination team is in place for any inpatient child older than 12 years in 42% of hospitals, in 42% only for "fragile" children. A centralized in-hospital immunization service is an emerging model that may contribute to increase compliance to vaccination of fragile patients and to fight against vaccination hesitancy.